2010
DOI: 10.1111/j.1365-3059.2010.02315.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on RNA silencing of a negative‐stranded RNA plant virus: Citrus psorosis virus

Abstract: Citrus psorosis virus (CPsV), genus Ophiovirus, causes a bark scaling disease of citrus. CPsV virions are kinked filaments with three negative-stranded RNA molecules (vRNA) and a 48 kDa coat protein. The effect of temperature on symptom expression, virus accumulation and RNA silencing was examined in sweet orange seedlings (Citrus sinensis) graft-inoculated with three different CPsV isolates and grown in a glasshouse at 26 ⁄ 18°C or 32⁄ 26°C (day⁄ night). Most plants kept in the cooler glasshouse showed a shoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 29 publications
4
34
0
1
Order By: Relevance
“…Virus induced gene silencing mechanism (VIGS) is evidenced by the presence of specific siRNA for RNA1, RNA2, and RNA3 of CPsV in infected plants (Velázquez et al, 2010). We also observed VIGS induction through cp specific siRNA accumulation in the inoculated NTi plants (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…Virus induced gene silencing mechanism (VIGS) is evidenced by the presence of specific siRNA for RNA1, RNA2, and RNA3 of CPsV in infected plants (Velázquez et al, 2010). We also observed VIGS induction through cp specific siRNA accumulation in the inoculated NTi plants (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…The amount of CPsVderived small RNAs (CPsV-sRNAs) slightly increased at 32/26°C, with the ratio of CPsV-sRNA/vRNA being higher at 32/26°C than at 26/18°C. These results suggest that CPsV infection induces RNA silencing in citrus plants, that symptom intensity is associated with virus accumulation, and temperature increase enhances the RNA silencing response of citrus plants and decreases virus accumulation [76].…”
Section: Biological Indexingmentioning
confidence: 74%
“…The study reported that the observed CPsV resistance was due to preactivated RNA silencing rather than the siRNA accumulation levels in the ihp-CP transgenic sweet orange plants prior to virus challenge [49]. Virus induced gene silencing (VIGS) is evidenced by the presence of specific siRNA molecules for RNA1, RNA2, and RNA3 of CPsV in infected plants [76]. Reyes et al [49] observed also VIGS induction through CP specific siRNA accumulation in the inoculated plants.…”
Section: Genetic Engineering and Disease Control In Citrusmentioning
confidence: 99%
See 1 more Smart Citation
“…Citrus plants infected with the ophiovirus CPsV have more severe symptoms in cooler greenhouses (16/18°C) (day/night) than in warmer greenhouses (32/26°C) (Velázquez et al, 2010), and virus titers parallel the symptom intensity. Outbreaks of virus diseases are often associated with low temperatures, while at high temperatures viral symptoms are often attenuated and plants can recover from virus infection (see Chapter 14, Section III, A, 3, b, ii for heat therapy).…”
Section: Environmental Factorsmentioning
confidence: 99%